Penggunaan Media Sosial Untuk Memasarkan Abon Pada UKM Abon Hasanah Di Desa Kediri Selatan Kabupaten Lombok Barat - Nursanty, Ida Ayu; Baehaki Syakbani; Rusli Amrul; Erviva Fariantin; I Nengah Arsana; I Made Murjana; M. Wahyullah; Nendy Pratama Agusfianto; Elvina Setiawati; Yusi Faizathul Octavia (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This community service program aims to support Micro, Small, and Medium Enterprises (MSMEs) in promoting shredded meat products (abon) to enhance public awareness and reach potential consumers. One of the main strategies implemented is the utilization of social media, particularly through the creation of an Instagram business account designed to build consumer trust in the product. The program was conducted in three stages: initial interviews and discussions, training and mentoring, and evaluation of MSME progress. The training focused on effective techniques for managing social media accounts, while mentoring involved monitoring the implementation of digital strategies and assessing the use of Instagram as a promotional platform. The results indicate that the shredded meat product has gained wider recognition among potential consumers, who consider it worth purchasing due to its savory taste and nutritional value as a daily food complement. Therefore, this community service program successfully expanded the market reach of abon through an appropriate digital marketing strategy.